Analisis Struktur Melodi dan Makna Lagu “Sayur Kol” Karya Punxgoaran - Eben Ezer Sormin; Junita Batu Bara; Emmi Simangunsong (Journal of Music Science, Technology, and Industry, 2023)
Purpose: This research discusses about analysis of the melodic structure of Sayur Kol by Punxgoaran. Sayur Kol was published in 2017. The theoretical basic used in this research is William P. Malm's theory to get a musicological study, and Ferdinand de Saussure's semiotic theory to explain the meaning of this song. The song Sayur Kol by Punxgoaran was performed in the Batak language with Rock and Punk nuances with drums, electric guitars, and bass guitars. Method: In this thesis, the writer uses a qualitative descriptive analysis method. Results and Discussion: The results of the study of the melodic structure of the Sayur Kol song are Song Form with 2 parts consisting of A (a, a'), B (b, b') and the song Sayur Kol performed by Punxgoaran consists of the Intro, the beginning, continuation part, chorus part, interlude part, and outro part. Implication: The meaning contained in song Sayur Kol is about the personal story of the creator, Guido Virdaus Hutagalung, expressing a picture of the situation of the people of North Sumatra when they meet each other and strengthen the relationship between fellow tribes, especially the Toba Batak tribe. Punxgoaran loves and supports the preservation of Batak Cultural Arts.